2013
DOI: 10.1186/1471-2296-14-106
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ information needs, self-efficacy and influences on consulting for childhood respiratory tract infections: a qualitative study

Abstract: BackgroundAcute respiratory tract infection (RTI) is the most common reason why parents consult primary care in the UK. Little is known about parents’ perceptions of what may help them to make an appropriate decision to consult when their child is ill and how to improve self-care.Using qualitative methods, this study aimed to explore parents’ views on support and information needs prior to consulting when children have RTIs with cough, and identify the triggers and barriers to consulting primary care.Methods7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(151 citation statements)
references
References 26 publications
3
144
2
2
Order By: Relevance
“…In previous work (Ingram et al, 2013) we found that the Health Belief Model (Rosenstock et al, 1994) was useful for understanding the parent beliefs which influenced their decision to consult. In particular, the constructs of perceived severity of the illness, perceived susceptibility to the illness, self-efficacy in relation to home management of the illness, perceived benefits of consulting, and cues to action (i.e.…”
Section: Parental Consulting and The Health Belief Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous work (Ingram et al, 2013) we found that the Health Belief Model (Rosenstock et al, 1994) was useful for understanding the parent beliefs which influenced their decision to consult. In particular, the constructs of perceived severity of the illness, perceived susceptibility to the illness, self-efficacy in relation to home management of the illness, perceived benefits of consulting, and cues to action (i.e.…”
Section: Parental Consulting and The Health Belief Modelmentioning
confidence: 99%
“…Although mainly self-limiting, they are a significant cause of concern for parents because of impacts on the child and family, and concerns about serious illness (Cornford et al, 1993;Kai, 1996a,b). Parents' decision to consult is influenced by perceived threat severity (Wyke et al, 1990;Cornford et al, 1993;Kai, 1996a;Neill, 2000;Ingram et al, 2013), the perceived benefits of consulting, and an expectation of assessment, information, advice or treatment (Kai, 1996a;Neill, 2000;Ingram et al, 2013). Parents are uncertain how to assess illness severity (Kai, 1996a;Francis et al, 2008;Neill, 2010;Ingram et al, 2013) and when to consult (Neill and Carter, 2012;Ingram et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have either examined communication within the consultation itself without asking participants what they were thinking 25,[34][35][36][37] or interviewed participants without an accurate record of what was actually said within the consultation. 15,38 Participants in our study may have modified their behavior because they knew they were being video recorded, although both parents and clinicians assured us these consultations did not seem different to them. This study recruited parents from a wide range of neighborhoods, and although we deliberately included parents from a wide range of ethnicities (including families from the Black African and Eastern European communities), very few of Asian ethnicity were recruited.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Previous studies have reported similar findings that mothers felt ambiguity about their appropriateness of management [34] [37]. Neill et al…”
Section: Discussionmentioning
confidence: 52%
“…Langer et al reported that mothers' concern was closely linked to the cause of fever when their children had fever [33]. Ingram et al also reported that all mothers of children who had cough referred to multiple causes before deciding on what to do [34]. Therefore, a lack of information about the causes of the illness is particularly important when we consider the uncertainty of mothers of children with ACI.…”
Section: Discussionmentioning
confidence: 99%